Berberine hydrochloride mitigates acute pancreatitis by suppressing the TLR4/IκBα/NFκB pathway. Issue 1 (1st January 2020) - Gu, Huali; Liu, Aiguo; Ma, Weiping; Ni, Jianmin; Ma, Chengtai; Zhou, Xiumei; Liu, Zhenfang; Xia, Di; Tian, Xintao; Shi, Lei; Zhu, Liang
Abstract : Severe acute pancreatitis (SAP) usually causes multiple-organ dysfunction syndrome and exhibits a high mortality rate. It has been previously reported that berberine, as a dominant alkaloid, can be effectively used against inflammation. However, there is limited data on the effects of berberine hydrochloride (BBRH) on inflammation in SAP rat models. Male Sprague–Dawley rats were given preliminary intraperitoneal injections of BBRH 30 min prior to retrograde infusion of 5% sodium taurocholate in their biliopancreatic ducts. The rats were sacrificed 12 h after taurocholate administration, and tissues and blood samples were then acquired for histological, chemical, and molecular analyses. The SAP models exhibited enhanced edema, ascitic fluid volume, neutrophil infiltration, serum amylase and lipase levels, and interleukin (IL)-6, tumor necrosis factor-α, and IL-1β levels, and reduced IL-10 concentration, while BBRH administration reversed these changes. Further study showed that in the SAP model, protein and mRNA levels of nuclear factor kappa-light-chain-enhancer of activated B (NFκB) p65 and toll-like receptor 4 (TLR4) were increased and inhibitor of nuclear factor kappa B (IκBα) expression was decreased, while pretreatment with BBRH significantly decreased the activation of the TLR4/IκBα/NFκB pathway. The data obtained displayed that BBRH mitigated acute pancreatitis by suppressing the TLR4/IκB/NFκB pathway.